Understanding quartz crystals and oscillators - Cerda, Ramon M. (Artech House, 2014)
Quartz, unique in its chemical, electrical, mechanical, and thermal properties, is used as a frequency control element in applications where stability of frequency is an absolute necessity. Without crystal controlled transmission, radio and television would not be possible in their present form.